DESIGN AND DEVELOPMENT OF WAREHOUSE MANAGEMENT INFORMATION SYSTEM (CASE : UD. DEWA JAYA): Rancang Bangun Sistem Informasi Manajemen Pergudangan (Studi Kasus UD. Dewa Jaya) - Rofi Yansyah, Moh Zulfikar; Utami, Ardhini Warih (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2023)
information technology in this era is one of the main tools that support human activities in various fields such as information processing and communication. With the help of information technology, operational and production processes will become more effective and efficient. UD Dewa Jaya is a company engaged in the business of producing ceramics and selling ceramics from its products or using other brands. The company has several places for product storage or warehouses, each with different functions. Warehouse A is intended for storing special ceramic products that have been ordered from manufacturers, while warehouse B is for storing special products with granite types. The company faces several issues in the process of managing and recording product stocks and transactions. The use of space in the warehouse has not been strategically organized, resulting in poorly arranged positions of items in the warehouse. This research is aimed at assisting the company in managing and recording items in the warehouse and facilitating the process of product allocation with the help of product classification. Product classification determines the position or location of items in the warehouse based on their categorized class. With this research, it is hoped that the company can determine the positions and placements of items in the warehouse based on the categorized product classes. This will also ease the company in determining evaluations and sales strategies for products that have been grouped and categorized by the system. Using a web-based application will make it easier for the company to use the system, as technologies such as computers and smartphones are already used as operational media for the company.